2009
DOI: 10.1021/jf901462s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Salvia miltiorrhiza (Danshen) Collected from Different Locations in China

Abstract: The chemical characteristics of Salvia miltiorrhiza , also called "danshen" in China, were investigated on the basis of the simultaneous quantitative determination of 13 hydrophilic and lipophilic compounds, namely, protocatechuic acid, protocatechuic aldehyde, caffeic acid, ferulic acid, isoferulic acid, rosmarinic acid, salvianolic acid B, salvianolic acid A, dihydrotanshinone I, przewalskin, cryptotanshinone, tanshinone I, and tanshinone IIA, in 74 samples collected from different locations using ultraperfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…Pharmacol-ogical studies established that these compounds possessed anti-ischemic, antioxidant, and antitumor activities [9,10]. Some analytical techniques were utilized for separation and identification of constituents in RSM, such as high-performance thin-layer chromatography (HPTLC), high-performance liquid chromatography (HPLC), ultra-performance liquid chromatography (UPLC), and liquid chromatography hyphenated with tandem mass spectrometry (LC-MS/MS) [11][12][13]. However, HPTLC had a disadvantage of low resolution, which resulted in inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacol-ogical studies established that these compounds possessed anti-ischemic, antioxidant, and antitumor activities [9,10]. Some analytical techniques were utilized for separation and identification of constituents in RSM, such as high-performance thin-layer chromatography (HPTLC), high-performance liquid chromatography (HPLC), ultra-performance liquid chromatography (UPLC), and liquid chromatography hyphenated with tandem mass spectrometry (LC-MS/MS) [11][12][13]. However, HPTLC had a disadvantage of low resolution, which resulted in inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The lipophilic pigments from the reddish root and rhizome consist of abietane quinone diterpenoids (Nakao and Fukushima, 1934), largely tanshinone IIA, cryptotanshinone, and tanshinone I (Zhong et al, 2009). These are highly bioactive.…”
mentioning
confidence: 99%
“…Similarity was analyzed by the Chromatographic Fingerprint of Traditional Chinese Medicine software (Version 2004A), which was developed by the Chinese Pharmacopoeia Committee [12,21]. This software evaluates similarity based on correlative coefficient calculations for fingerprint chromatograms.…”
Section: Discussionmentioning
confidence: 99%
“…The stability was tested by analyzing the same sample solution after being prepared in 0, 2,4,6,8,12, and 24 h. The RSD values of the eight standards ranged from 1.6% to 3.3%. The data revealed that the stability of the solution was acceptable.…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation